Central bank institutional structure and effective central banking: cross-country empirical evidence - Iftekhar Hasan; Loretta J. Mester (Bank of Finland, 2008)
Over the last decade, the legal and institutional frameworks governing central banks and financial market regulatory authorities throughout the world have undergone significant changes. This has created new interest in better understanding the roles played by organizational structures, accountability and transparency in increasing the efficiency and effectiveness of central banks in achieving their objectives and ultimately yielding better economic outcomes. Although much has been written pointing out the potential role institutional form can play in central bank performance, little empirical work has been done to investigate the hypothesis that institutional form is related to performance. This paper attempts to help fill this void
URN:NBN:fi:bof-20140807174
Keywords: 330